Oranjemund Shipwreck : a composition analysis of the Pewter Kitchen Ware And their conservation aspects - Loubser, Maggi (University of Pretoria, 2022)
Mini Dissertation (MSocSci (Tangible Heritage Conservation))--University of Pretoria, 2021.